The impact of online technologies and english medium instruction on university lectures in international learning contexts: a systematic review - Querol-Julián, Mercedes; Crawford Camiciottoli, Belinda (ESP Today, 2019)
This paper addresses how the university lecture is evolving in response to new realities in international higher education driven by two important trends: innovative online instructional technologies and the rise of English Medium Instruction (EMI). Following a brief review of the lecture as the core instructional channel in universities, we offer a detailed overview of the new technology-driven lecture formats that are now available to learners worldwide. We then shift the focus to the role of EMI, with particular attention to understanding how both instructors and students view this relatively new approach to learning. This was accomplished through a systematic review of EMI-related literature available in scholarly databases. Findings showed that most research has focused on the language-related issues of learners, and little attention has been paid to the crucial issue of lecture comprehension, which is mainly caused by the low level of proficiency of students/instructors and domain-specific vocabulary. Moreover, studies have almost exclusively addressed face-to-face settings, indicating a need to expand EMI research to include online lecture settings that are increasingly frequent in international higher education. This paper contributes to the body of knowledge relating to new trends in how lectures are experienced and perceived in international educational settings.
Keywords: international students; EMI; lecture formats; technology-driven lectures; lecture comprehension; Emerging; Scopus